PENGARUH LOCUS OF CONTROL TERHADAP STRATEGI OPERASIONAL DAN KINERJA UMKM DI KABUPATEN MUNA PROPINSI SULAWESI TENGGARA DENGAN LINGKUNGAN SEBAGAI VARIABEL MODERATOR - Setiawan, Fanny Andriani; Suhendah, Rousilita (Jurnal Ekonomi, 2016)
This study aimed to examine the effect of locus of control on operational strategy and performance of UKM in districts muna to the environment as a moderator variable. This research data is the primary data obtained through a questionnaire given to entrepreneurs traditional weaving in Lohia and Kontunaga in Muna district. The results showed that the locus of control significantly influence the operational strategies of UKM, but have a negative relationship. This happens because the weaving entrepreneurs still have the belief that there are outside forces that can control the things that happen in life as their chance and luck. The results also show that the interaction of locus of control and environmentally significant effect on the operational strategy of UKM. This means that the environment of uncertainty faced by employers weaving cause uncertain situation for employers weaving to make operational strategy. The results also show that the locus of control have a significant effect on the performance of UKM, and interaction locus of control and the environment also have a significant effect on the performance of UKM. Locus of control is a significant negative effect on the performance of UKM indicate that employers are still weaving industry has knowledge of the weaving industry for generations and very weak in taking the initiative for the development of the weaving industry so that the performance of UKM has declined.